Microscopic spheroidal particles obtained by laser cutting - Cabanillas, E. D. (2005)
In this work we study the characteristics of the particles ejected from the cutting zone of a SAE 1010 steel while using a CO2 gaseous laser with the purpose of determining the feasibility to use this technique in the production of microscopic particles for nuclear applications [2] as well as for other scientific and technological uses [1].